ASSESSMENT OF RURAL WOMEN PARTICIPATION IN RICE PRODUCTION, PROCESSING AND MARKETING IN ZONE A, KANO STATE, NIGERIA - Kabiru, M., K.; Sani, R., M.; Ibrahim, A., A.; Jibril, S., A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study assessed the rural women participation in rice production, processing and marketing in Zone A, Kano State, Nigeria. A Multistage sampling technique was used to select 377 rural women farmers for the study. Data were collected using structured questionnaire and analyzed using both descriptive and inferential statistics. The study revealed that rural women had attain one form of formal education and had a mean age of 38 years with a mean household size of 8 persons. The result also revealed that the mean farm size was 2ha for rice production and had mean rice production experience of 11years respectively. Furthermore, rural women had mean years of rice processing and marketing of 10 and 8year with a mean annual income from rice production, processing and marketing of ₦174,720.00, ₦28,620.00 and ₦24,297.00 respectively. The result revealed that majority (59.9%, 73.5% and 66.6%) of the respondents were house-wife, married and practice polygamous family setting respectively, most (82.2%) had rice production, processing and marketing as primary occupation. The result also revealed that about half (49.9% and 25.5%) had average perception on food security and food production while (40.8%) had profit and income as their household priority in rice production, processing and marketing. The Probit results, showed that education, age and membership were found significant (P<0.05) respectively, while, farm size, rice farming experience and household size were found significant (P<0.01) respectively, with Pseudo R2 0.1815. The study concluded that women participation in rice production in the study area is significant, due to their involvement in the three forms of participation identified in the study. Rural women were actively involved in rice production, with 70%, processing, with 80% and marketing, with 60% selling rice in local markets. The study recommends government should develop and devise ways to encourage women's participation in cooperatives groups. Further research should explore innovative solutions to enhance women's participation and benefits in the rice value chain and by empowering rural women in rice production, processing, and marketing, we can unlock their potential, improve livelihoods, and contribute to food security and poverty reduction in Kano State.